La expresión del lamento en la episitolografía griega de tema erótico a la luz de las teorías retóricas griegas: las cartas de Alcifrón - Vicente Sánchez, Ana Cristina (2004)
The expression of the lament in erotic Greek epistolograpby from the perspective of rhetorical Greek theories: Alcipbran's Letters". A study about the way lo express lament or complaint in Alcipbrons Letters and its relationship with rhetorical Greek prescriptions.
Keywords: Alcifrón; Cartas; Literatura griega; Literatura erótica